APPLICATION OF UCD METHOD IN DESIGNING SIMPLE SAVINGS APPLICATION AT MTS AL-MANAR BASED ON WEBSITE - Utami, Nadya; Zakir, Ahmad; Rahayu, Eka (Bahasa Indonesia, 2025)
Student savings information system to avoid errors in the saving process, one of the problems that occurs at MTS Al-Manar Medan is that the student savings management system at MTS Al-Manar still uses manual methods. With information conveyed orally, this causes the information received by students to be less accurate, not up to date, and easily lost and forgotten. This is less effective because the lack of accuracy in conveying and receiving information becomes an obstacle in processing student savings. This system is designed to make it easier to manage student savings as expected. The main focus of this system is to avoid errors in recording, loss of savings books, savings books, and managing savings data. You can use online media in the form of a website to make it easier for treasurers to manage savings and compile reports quickly and accurately. Researchers created a simple websitebased savings application at MTS Al-Manar using the UCD method. So that MTS Al-Manar Medan uses it, and provides optimal benefits for all parties involved. The goal with this savings application is to make it easier for school administration to input student savings data, and students can monitor each student's savings data on the savings application portal, thereby avoiding school savings application administrator errors.